Virtual Reality Human Computer Interaction - Tang, Xin‐Xing (IntechOpen, 2012)
At present, the virtual reality has impact on information organization and management and even changes design principle of information systems, which will make it adapt to application requirements. The book aims to provide a broader perspective of virtual reality on development and application. First part of the book is named as "virtual reality visualization and vision" and includes new developments in virtual reality visualization of 3D scenarios, virtual reality and vision, high fidelity immersive virtual reality included tracking, rendering and display subsystems. The second part named as "virtual reality in robot technology" brings forth applications of virtual reality in remote rehabilitation robot-based rehabilitation evaluation method and multi-legged robot adaptive walking in unstructured terrains. The third part, named as "industrial and construction applications" is about the product design, space industry, building information modeling, construction and maintenance by virtual reality, and so on. And the last part, which is named as "culture and life of human" describes applications of culture life and multimedia-technology.